ANALISIS KELEMBAGAAN NELAYAN KAPAL SLEREK DI DESA PENGAMBENGAN KECAMATAN NEGARA KABUPATEN JEMBARANA BALI: STUDI HUBUNGAN KERJA DAN DINAMIKA PENDAPATAN NELAYAN - Agus Purwanto; Yvonne Indrawati Pattinaja; Leopold Arthur Tomasila (Universitas Pattimura, 2021)
Economic relations between capital owners and fishermen will lead to institutional changes (rules of the game) that are obeyed together to maintain the continuity of fishing activities. Institutional that occurs in coastal communities is an interaction between economic agents to achieve certain goals such as welfare. The purposes of this study are 1) Analyzing institutions in fishing efforts using Slerek boat related to working relationship patterns and income dynamics 2) Analyzing the institutional impact on the employment of coastal communities. Based on the results of this qualitative research obtained data that the institutions formed in fishing business activities using slerek boat are the result of continuous interaction so that an unwritten pattern of rules of the games is created that comes from the agreement of the economic agents involved in it. Institutional related labor relations are dominated by agreements between land, sea and patching skippers. The most prominent working relationships appear in the profit sharing system consisting of three systems, namely the system for the light of the moon, the system for three and the clean system of the beach. Institutional related income dynamics are influenced by fish prices, the number of catches, the revenue sharing system implemented, operational costs. The impact caused by the existence of economic institutions on fishing business activities using slerek boat to the absorption of labor is the amount of labor needed in one pair of slerek boat is 46 people.